2017
DOI: 10.1021/acs.jnatprod.7b00325
|View full text |Cite
|
Sign up to set email alerts
|

Potential Anti-inflammatory Effects of the Fruits of Paulownia tomentosa

Abstract: As part of an ongoing search for new natural products from medicinal plants to treat respiratory disease, six new compounds, a dihydroflavonol (1) and five C-geranylated flavanones (3, 6, 8, 13, and 14), and 13 known compounds were isolated from mature fruits of Paulownia tomentosa. The structures of the new compounds were determined via interpretation of their spectroscopic data (1D and 2D NMR, UV, IR, ECD, and MS). In biological activity assays with human alveolar basal epithelial cells, the expression of TN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…The values presented in Table 3 suggest that glucosylation or rhamnosylation at positions C-7 or C-3 presumably produce steric hindrances that prevent molecules from binding to enzymes 126 . In addition, a comparison of an anti-elastase potential of apigenin and apigenin 4 0 -O-b-D-glucoside leads to the conclusion that glucosylation of the hydroxyl group in B-ring also reduces its activity 70,77 .…”
Section: Inhibitory Effect Of Flavonoids On Elastase Activitymentioning
confidence: 99%
“…The values presented in Table 3 suggest that glucosylation or rhamnosylation at positions C-7 or C-3 presumably produce steric hindrances that prevent molecules from binding to enzymes 126 . In addition, a comparison of an anti-elastase potential of apigenin and apigenin 4 0 -O-b-D-glucoside leads to the conclusion that glucosylation of the hydroxyl group in B-ring also reduces its activity 70,77 .…”
Section: Inhibitory Effect Of Flavonoids On Elastase Activitymentioning
confidence: 99%
“…The bark, leaves, and flowers of Paulownia trees have been used in traditional medicine to treat infectious and inflammatory diseases in East Asia [2]. Pharmacological studies showed that the extracts from P. tomentosa could inhibit the protein tyrosine phosphatase 1B and α-glucosidase, which are important therapy targets of obesity and diabetes treatment [3], suppress the production of IL-6 and TNF-α in LPS-stimulated RAW 264.7 macrophages [2], and treat airway inflammation [4]. It has been also demonstrated that methanolic extracts of P. tomentosa flowers are active against EV71 of hand, foot, and mouth disease [5].…”
Section: Introductionmentioning
confidence: 99%
“…The ECD spectrum of 2 contained the characteristic CEs induced by C-4 ketone carbonyl in its flavanonol framework, namely, a positive one at λ max 320 nm ( Figure 4 ). The absolute configuration of C-2 and C-3 was thus proposed to be 2R, 3R [ 11 , 13 ]. Subsequently, we performed computational predictions of NMR chemical shifts of both the possible isomers 2R, 3R, 2″R and 2R, 3R, 2″S ( Figure 3 ) using the GIAO method at the mPW1PW91/6-311G(d,p) level with the conductor polarizable calculation model (CPCM) in MeOH [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…The shielding constants were converted into unscaled chemical shifts (δ u ) by referencing TMS (δ u = σ TMS − σ Cal ), where the σ TMS was the shielding constant of TMS calculated at the same level. The NMR chemical shifts of the isomers were obtained by Boltzmann averaging the 1 H and 13 C NMR chemical shifts of the stable conformers. The calculated NMR properties of optimized structures were averaged based upon their respective Boltzmann populations, and calculations of DP4+ probability analysis were facilitated by the Excel sheet (DP4+) provided by Grimblat et al [8].…”
Section: Computation Detailsmentioning
confidence: 99%